Poverty measurement : meanings, methods, and requirements - Gunewardena, Dileni (Colombo : Centre for Poverty Analysis, 2004)
With reference to Sri Lanka.
Includes bibliographical references (p. 160-188) and index.
Keywords: Poverty -- Sri Lanka; Poverty -- Sri Lanka